PERLINDUNGAN HUKUM TERHADAP PEMENANG LELANG BENDA BERGERAK NON EKSEKUSI SUKARELA YANG TIDAK MENDAPATKAN AKTA RISALAH LELANG DI PT. IBID BALAI LELANG PEKANBARU - Al Arif; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study aims to determine the criminal threat of online debt debt collector to online loan debtors in debt collection and to find out the obstacles or obstacles to the police in the criminal act of violence committed online debt collector loans to online loan debtors that occur in Riau province. The research method used is a descriptive sociological juridical method, where research data are obtained from field study and library research, the data analysis is done interview.Based on the results of the study, criminal acts of violence committed online debt collector loans to online loan borrowers are very detrimental to the public because in debt collection to online debt borrowers have violated the ethical rules of debt collectors in Bank Indonesia Circular Letter Number 14/17 / DASP / 2012 concerning the Implementation of Card-Based Payment Instrument Activities debt collection and have violated the ITE Law. In the criminal act of threat of violence committed by this online loan debt collector, the police experienced obstacles in finding the perpetrators of the crime, especially what was done by the debt collector through electronic media or online.Keywords: Threat of Violence, Debt Collector, Debtors